Functional diversity of fish communities in two tropical estuaries subjected to anthropogenic disturbance. Issue 1 (15th November 2016) - Dolbeth, M.; Vendel, A.L.; Pessanha, A.; Patrício, J.
Abstract: The functional diversity of fish communities was studied along the salinity gradient of two estuaries in Northeast Brazil subjected to different anthropogenic pressures, to gain a better understanding of the response of fish communities to disturbance. We evaluated functional complementarity indices, redundancy and analysed functional composition through functional groups based on combinations of different traits. The fish communities in both estuaries share similar functions performed by few functional groups. The upstream areas had generally lower taxonomic, functional diversity and lower redundancy, suggesting greater vulnerability to impacts caused by human activities. Biomass was slightly more evenly distributed among functional groups in the less disturbed estuary, but total biomass and redundancy were lower in comparison to the urbanized estuary. The present findings lend strength to the notion that the less disturbed estuary may be more susceptible to anthropogenic impacts, underscoring the need for more effective conservation measures directed at this estuary. Highlights: Functional diversity was studied in two tropical estuaries with different impacts. Fish communities share similar functions performed by few functional groups. Distinct salinity sectors exhibit different degrees of vulnerability. The less impacted estuary was considered more vulnerable to disturbance. More effective management measures are suggested for both estuaries.